Becoming an Antinatalist: Biographical Ordering of Meaning in the Face of Trajectories of Suffering - Gronek-Żywicka, Halszka (Studia Socjologiczne, 2026)
Discussions of antinatalism most often frame it as either a philosophical doctrine or an ethical position. The author proposes a different perspective, approaching antinatalism not as a theory-derived stance but as a biographically constructed form of individual social agency in response to experiences of suffering and existential uncertainty. The analysis is based on Fritz Schütze’s method of biographical reconstruction with the study comprising ten individual interviews conducted in accordance with the full procedure of the narrative autobiographical interview. The findings indicate that antinatalism may emerge affectively, as a response to biographical trajectories of suffering. In retrospective narration, these experiences are interpretatively and normatively processed, leading to the formation of a coherent and socially communicable symbolic universe. Drawing on Alfred Schutz’s phenomenology and Peter L. Berger’s and Thomas Luckmann’s sociology of knowledge, the paper demonstrates how moments of breakdown in meaning lead to its reconstruction, showing narrative as a key social mechanism of sense-making. Moreover, the findings reveal the defensive nature of antinatalism: radical attitudes function as a response to stigmatization, while the stance itself appears as a paradoxical form of responsibility in the context of global threats.